Cysteine, Glutathione, and Thiol Redox Balance in Astrocytes - Gethin J. McBean (MDPI AG, 2017)
This review discusses the current understanding of cysteine and glutathione redox balance in astrocytes. Particular emphasis is placed on the impact of oxidative stress and astrocyte activation on pathways that provide cysteine as a precursor for glutathione. The effect of the disruption of thiol-containing amino acid metabolism on the antioxidant capacity of astrocytes is also discussed.